(untitled) (Research, Society and Development, 2023)
Objective: to evaluate the level of self-esteem of high-risk pregnant women hospitalized in a public maternity hospital, describing them in terms of their socio-personal and obstetric characteristics, in addition to pointing out a possible correlation of these characteristics with the level of self-esteem. Methodology: this is a descriptive, cross-sectional study with a quantitative approach that was carried out with 30 high-risk pregnant women hospitalized in a public maternity hospital of high complexity. For data collection, a socio-personal and obstetric characterization questionnaire was used. Self-esteem was assessed using the Rosenberg Self-Esteem Scale. The collected data were analyzed using the IBM Statistical Package for the Social Sciences version 20.0. The significance level adopted was p<0.05. Results: the obstetric variable “Is your current pregnancy desired by you?” was the only one with a significant correlation with self-esteem (p = 0.029) among those studied, so that there was no significance for the correlation between the self-esteem score and the socio-personal data studied (p<0.05). Most (83%) had a low level of self-esteem based on the analysis of the scores obtained. Conclusion: it is concluded that the level of self-esteem of pregnant women hospitalized in a public maternity hospital was considered low. In addition, it was shown that high-risk pregnant women who do not want the current pregnancy have lower self-esteem than those who do.